2022
DOI: 10.1155/2022/7098121
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology and Molecular Docking Verify the Mechanism of Qinshi Simiao San in Treating Chronic Prostatitis in the Rat Model

Abstract: Background. Using network pharmacology and molecular docking, this study aimed to explore the active pharmaceutical ingredients (APIs) and molecular mechanism of Qinshi Simiao San (QSSMS) in the treatment of chronic prostatitis (CP) and verify our findings in the rat model. Methods. The APIs of QSSMS and the common targets of QSSMS and CP were screened from the TCMSP database. The STRING database and Cytoscape software were used to construct the network graph. The enriched GO and KEGG pathways were displayed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Modified Haoqin Qingdan Decoction consists of Qing Hao 4.5g, Huang Qin 9g, Zhi Ke 4.5g, Zhu Ru 4.5g, Chen Pi 4.5g, Ban Xia 4.5g, Fu Ling 9g, Bi Yusan [consisting of Qing Dai, Hua Shi and Gan Cao] 9g, Shen Qu 4.5g, Shan Zha 4.5g, Mai Ya 4.5g with the Latin names Herba Artemisiae annuae, Scutellaria baicalensis Georgi, Fructus Aurantii Immaturus, Caulis Bambusae in Taeniam, Pericarpium Citri Reticulatae, Rhizoma Pinelliae, Poria, Biyu powder [ consisting of Indigo Naturalis, Talcum and Radix Glycyrrhizae], Massa Medicata Fermentata, Crataegi Fructus and Fructus Hordei Germinatus, respectively. The drug was prepared according to the pharmacological experimental methodology of Chinese medicine 11,12 : firstly, the drug was soaked for 30 min, the first decoction was boiled with 10 times the amount of water, boiled and filtered after 40 min of low heat. The second decoction was filtered by adding 8 times the amount of water, boiled and filtered after 40 min of low heat; the 2 filtrates were combined and then the filtrate was concentrated to 1g/1mL of the raw drug solution.…”
Section: Methodsmentioning
confidence: 99%
“…Modified Haoqin Qingdan Decoction consists of Qing Hao 4.5g, Huang Qin 9g, Zhi Ke 4.5g, Zhu Ru 4.5g, Chen Pi 4.5g, Ban Xia 4.5g, Fu Ling 9g, Bi Yusan [consisting of Qing Dai, Hua Shi and Gan Cao] 9g, Shen Qu 4.5g, Shan Zha 4.5g, Mai Ya 4.5g with the Latin names Herba Artemisiae annuae, Scutellaria baicalensis Georgi, Fructus Aurantii Immaturus, Caulis Bambusae in Taeniam, Pericarpium Citri Reticulatae, Rhizoma Pinelliae, Poria, Biyu powder [ consisting of Indigo Naturalis, Talcum and Radix Glycyrrhizae], Massa Medicata Fermentata, Crataegi Fructus and Fructus Hordei Germinatus, respectively. The drug was prepared according to the pharmacological experimental methodology of Chinese medicine 11,12 : firstly, the drug was soaked for 30 min, the first decoction was boiled with 10 times the amount of water, boiled and filtered after 40 min of low heat. The second decoction was filtered by adding 8 times the amount of water, boiled and filtered after 40 min of low heat; the 2 filtrates were combined and then the filtrate was concentrated to 1g/1mL of the raw drug solution.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that COX-2 is an important rate-limiting enzyme involved in PGF 2α transformation and synthesis, which supports its potential role in the treatment of PD. [16][17][18] Ginger (Rhizoma zingiberis, RZ) originates from Zingiber officinale Rosc. and was first described in the Shennong's Classic of Materia Medica (25-220 C.E.).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that COX-2 is an important rate-limiting enzyme involved in PGF 2α transformation and synthesis, which supports its potential role in the treatment of PD. 16–18…”
Section: Introductionmentioning
confidence: 99%